A New Model to Correlate Solubility of Therapeutic Drugs in Supercritical Carbon Dioxide - Amrithaa, Raghavan; Garlapati, Chandrasekhar (Fine Chemical Engineering, 2024)
In this work, a new solubility model was proposed based on the enhancement factor concept. The proposed model is validated with the literature available solubility data of seventeen therapeutic drugs in supercritical carbon dioxide. The correlating ability of the proposed model was compared with the Chrastil model and Bartle et al. model. The global average absolute relative deviation (AARD) percentages of Chrastil, Bartle et al. and new models were 19.42%, 19.57% and 16.43%, respectively. Sublimation enthalpies of therapeutic drugs were calculated with a new model as well as with Bartle et al. model. The calculated sublimation enthalpies ranged between 8.32 to 180.23 kJ/mol and 19.5 to 280.26 kJ/mol for the Bartle et al. model and the Improved Bartle model, respectively. Finally, a statistical analysis was performed in terms of Alaike's Information Criterion (AIC) to differentiate models considered in this work.